Academic or vocational education? A comparison of the long-term wage development of academic and vocational tertiary degree holders - Kriesi, Irene [Verfasser]; Sander, Fabian [Verfasser] (My University, 2024)
„Education is a key determinant of wage development. The relationship between education and wages is particularly strong in countries with vocationally oriented educational systems and a clear distinction between general and vocational education, such as Germany and Switzerland. However, whether general and vocational education offer the same returns to education is an ongoing debate. Previous findings from international research are still inconclusive. Against this background and based on theoretical arguments from human capital and signalling theory and the task-specific learning-by-doing approach, our paper examines the long-term wage development of Swiss university and professional education degree holders from the time they obtain their tertiary degree until their late career. It asks how differences between the two groups in wage development may be explained. Our results, produced with regression decomposition methods, show that within the first 20 years after graduation, university degree holders experience steeper wage growth. An important reason for this difference is that university graduates move more often than vocational tertiary degree holders into well-paid labour market positions endowed with formal authority, management responsibility, and a large proportion of cognitive nonroutine tasks.“ (authors‘ abstract; BIBB-Doku)
Keywords: P 2.6 Hochschulabsolventen; G 1.3.3.1 Qualifikationsverwertung; 370; 330; Hochschulabsolvent; Akademiker; Ausbildungsabsolvent; Facharbeiter; Lohn; Lohnentwicklung; Bildungsertrag; Schweiz